Acute cerebellar stroke and middle cerebral artery stroke exert distinctive modifications on functional cortical connectivity: A comparative study via EEG graph theory - Vecchio, Fabrizio; Caliandro, Pietro; Reale, Giuseppe; Miraglia, Francesca; Piludu, Francesca; Masi, Gianvito; Iacovelli, Chiara; Simbolotti, Chiara; Padua, Luca; Leone, Edoardo; Alù, Francesca; Colosimo, Cesare; et al. (Clinical neurophysiology, 2019)
•Acute cerebellar stroke may determine changes in brain network architecture.•Optimal network structure is essential for proper information processing in the brain.•Functional abnormalities of the brain are found to be associated with the pathological changes in connectivity and network structures. We tested whether acute cerebellar stroke may determine changes in brain network architecture as defined by cortical sources of EEG rhythms. Graph parameters of 41 consecutive stroke patients (<5 days from the event) were studied using eLORETA EEG sources. Network rearrangements of stroke patients were investigated in delta, alpha 2, beta 2 and gamma bands in comparison with healthy subjects. The delta network remodeling was similar in cerebellar and middle cerebral artery strokes, with a reduction of small-worldness. Beta 2 and gamma small-worldness, in the right hemisphere of patients with cerebellar stroke, increase respect to healthy subjects, while alpha 2 small-worldness increases only among patients with a middle cerebral artery stroke. The network remodeling characteristics are independent on the size of the ischemic lesion. In the early post-acute stages cerebellar stroke differs from the middle cerebral artery one because it does not cause alpha 2 network remodeling while it determines a high frequency network reorganization in beta 2 and gamma bands with an increase of small-worldness characteristics. These findings demonstrate changes in the balance of local segregation and global integration induced by cerebellar acute stroke in high EEG frequency bands. They need to be integrated with appropriate follow-up to explore whether further network changes are attained during post-stroke outcome stabilization.